2022
DOI: 10.1038/s41598-022-20478-z
|View full text |Cite
|
Sign up to set email alerts
|

Identifying driving factors of urban land expansion using Google Earth Engine and machine-learning approaches in Mentougou District, China

Abstract: The research on driving mechanisms of urban land expansion is hot topic of land science. However, the relative importance of anthropogenic-natural factors and how they affect urban land expansion change are still unclear. Based on the Google Earth Engine platform, this study used the support vector machine classifier to extract land-use datasets of Mentougou district of Beijing, China from 1990 to 2016. Supported by machine-learning approaches, multiple linear regression (MLR) and random forests (RF) were appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…As an empirical estimation model, logistics regression is a data-driven rather than knowledgebased approach to the choice of predictor variables (Hu and Lo, 2007). Previous studies identified the significant factors that determine the potential for urban expansion and land-use changes (Park et al, 2011;Arsanjani et al, 2013;Musa et al, 2017;Aburas et al, 2017;Shafizadeh-Moghadam et al, 2017;Hassan and Elhassan, 2020;Cheng et al, 2022). This study used 12 factors driving the land-use change process and the data generated as Euclidean Distance maps in the ArcGIS environment (Figure 4).…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
“…As an empirical estimation model, logistics regression is a data-driven rather than knowledgebased approach to the choice of predictor variables (Hu and Lo, 2007). Previous studies identified the significant factors that determine the potential for urban expansion and land-use changes (Park et al, 2011;Arsanjani et al, 2013;Musa et al, 2017;Aburas et al, 2017;Shafizadeh-Moghadam et al, 2017;Hassan and Elhassan, 2020;Cheng et al, 2022). This study used 12 factors driving the land-use change process and the data generated as Euclidean Distance maps in the ArcGIS environment (Figure 4).…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
“…This expansion requires careful consideration of various factors, including the influence of urban heat islands on the environment, the introduction of environmental indices based on remote sensing data, and spatial patterns (Shi et al, 2011;Fan et al, 2022). In addition, it is crucial to consider accessibility factors, such as distance to major roads and city centres (Cheng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Urban growth in advanced countries was demonstrated to cause subtle landscape transformations [1][2][3][4] . Patch fragmentation, spatial polarisation in urban and non-urban land, simplification and homologation of natural landscapes are transformative processes characteristic of suburban and rural districts experiencing economic growth, population increase, and settlement expansion [5][6][7][8] . The resulting landscape matrix became particularly complex and spatially entropic, with a massive increase in the fractal dimension of individual patches as one of the most evident attributes of change [9][10][11][12] .…”
mentioning
confidence: 99%